High Efficiency Fast-Chargers for Lead-Acid Batteries. (6th December 2016) - Vorel, Pavel; Cervinka, Dalibor; Prochazka, Petr; Toman, Marek; Martis, Jan
Abstract : Fast-chargers developed for lead-acid batteries are presented in this contribution. The first charger (700 W) is matched to classical automotive applications (lead-acid batteries 12 V or 6 V). The second one (1500 W) was created for a traction lead-acid battery 48 V / 40 Ah of an electric scooter. Both of the chargers are equipped with a cascade control structure with master (outer) voltage control loop and slave (inner) current control loop. This way better stability of the control process is achieved than using parallel voltage and current control. The adjustable current limit can decrease the maximum charging current according to the actual size of the charged battery. The 12 V charger provides maximum current of 50 A which can help starting a car with an older or discharged battery. A DC/DC converter with high switching frequency and PWM control is the base of both chargers. Minimum size and weight as well as high efficiency were reached.